1997
DOI: 10.1295/polymj.29.752
|View full text |Cite
|
Sign up to set email alerts
|

Photoconductivity of a Polyimide with an Alicyclic Diamine Doped with N,N,N′N′-Tetramethyl-p-phenylenediamine

Abstract: ABSTRACT:Photoconductivity of a polyimide with an alicyclic diamine [the polyimide film prepared from pyromellitic dianhydride and diaminodicyclo hexylmethane Pl(PMDA/DCHM)], and an aromatic polyimide [the polyimide film prepared from pyromellitic dianhydride and oxydianiline PI(PMDA/ODA)] was investigated by the addition of an electron donor, N,N,N' N' -tetramethyl-p-phenylenediamine (TMPD). The addition of the electron donor increased the photocurrent generation of two polyimide films by about three orders o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
(11 reference statements)
2
13
0
Order By: Relevance
“…The increase in photocurrent generation by one order of magnitude for the PI(PMDA/DCHM) film after annealing is suggested to be due to the increase in the degree of molecular packing between polymer backbone intermolecularly. 22 Both PI(PMDA/DCHM) and PI(PMDA/DMDHM) films have pyromellitic imide moiety in their polymer backbone; the only difference is that DMDHM contains two methyl substituents. The photocurrent of PI(PMDA/ DMDHM) should have been observed if photoconductivity were due to pyromellitic imide moieties in the ground or excited state.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in photocurrent generation by one order of magnitude for the PI(PMDA/DCHM) film after annealing is suggested to be due to the increase in the degree of molecular packing between polymer backbone intermolecularly. 22 Both PI(PMDA/DCHM) and PI(PMDA/DMDHM) films have pyromellitic imide moiety in their polymer backbone; the only difference is that DMDHM contains two methyl substituents. The photocurrent of PI(PMDA/ DMDHM) should have been observed if photoconductivity were due to pyromellitic imide moieties in the ground or excited state.…”
Section: Measurementsmentioning
confidence: 99%
“…Under the same conditions at wavelengths where the absorbance of the films were the same. 22 these conditions, almost all of the poly(amide …”
Section: Introductionmentioning
confidence: 98%
“…[4][5][6]9 The electrical conduction behaviors of PMDA/ODA films have been investigated by several research groups. [10][11][12][13][14][15][16][17][18][19] Sawa et al 13 studied the electric conduction current of PMDA/ODA films at temperatures of 120-180 1C and applied electric fields of 4 À500 kV cm À1 . They concluded that the conduction in the PI films is caused by ionic hopping.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that both enhancement in the charge mobility and an increase in the number of electronic carriers in the bulk are necessary to improve the conductivity of PIs. Lee et al [17][18][19] investigated the photoconductivity of semi-aliphatic 4,4 0 -diaminodicyclohexylmethane (PMDA/DCHM) PI films. They reported that a charge-transfer complex is formed in the excited state when an optical absorption band assignable to weak intermolecular interactions is excited, and the charge-transfer complex subsequently produces charge carriers of radical cations and radical anions.…”
Section: Introductionmentioning
confidence: 99%
“…[1] In general, polyimides (PI) are prepared by a two-step process; first, diamines react with dianhydrides in aprotic polar solvents at room temperature to give poly(amide acid)s (PAA), the precursor of polyimides; second, poly (amide acid)s are converted to polyimides by either thermal or chemical imidization. Recently, new polyimides with various functional groups which show high solvent solubility, [2][3][4] high photosensitivity, [5][6][7] and photoconductivity, [8][9][10] have been actively investigated. Although polyimides have been widely used in microelectronics and space industry, their apparent color from yellow to brown has limited their application in optical communication and liquid crystal display devices.…”
Section: Introductionmentioning
confidence: 99%